2022
DOI: 10.1177/09622802221139233
|View full text |Cite
|
Sign up to set email alerts
|

Standard error estimation in meta-analysis of studies reporting medians

Abstract: We consider the setting of an aggregate data meta-analysis of a continuous outcome of interest. When the distribution of the outcome is skewed, it is often the case that some primary studies report the sample mean and standard deviation of the outcome and other studies report the sample median along with the first and third quartiles and/or minimum and maximum values. To perform meta-analysis in this context, a number of approaches have recently been developed to impute the sample mean and standard deviation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…Estimated mean age was calculated whenever articles reported the median age, using the quantile estimation method. 19 Extracted variables known to be relevant in genetic association studies are summarized in Table S3.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Estimated mean age was calculated whenever articles reported the median age, using the quantile estimation method. 19 Extracted variables known to be relevant in genetic association studies are summarized in Table S3.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…For continuous outcomes reported in median values and corresponding interquartile ranges, we estimated the sample mean and SD using the quantile estimation method, as previously described. 11,12…”
Section: Methodsmentioning
confidence: 99%
“…Apart from considerations on the outcome measure, two factors that strongly differentiate the performance of mean-based methods and median-based methods are (i) the proportion of primary studies reporting medians and (ii) the skewness of the outcome distribution in the primary studies. For (i), as the proportion of primary studies reporting medians increases, the performance of median-based methods often improves and the performance of mean-based methods often worsens [15,16,23], as one may expect. For (ii), when the outcome distribution is highly skewed, mean-based methods can perform poorly [15,16,23].…”
Section: Comparison Of Methodsmentioning
confidence: 97%
“…While most of the literature on mean-based methods has focused on better estimating the sample mean and standard deviation from S 1 , S 2 , or S 3 , another important consideration is the performance of such methods in the context of meta-analysis. McGrath et al [23] showed that using the imputed study-specific sample means and standard deviations in place of the actual (unreported) sample means and standard deviations in standard meta-analytic methods can severely underestimate the within-study SEs for studies reporting medians, which can result in negative downstream consequences in meta-analysis. Moreover, they described a bootstrap approach to better estimate the within-study SEs when using the mean estimators of McGrath et al [7] and Cai et al [12].…”
Section: Mean-based Methodsmentioning
confidence: 99%